2021
DOI: 10.18174/553273
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of seafloor litter on the Dutch continental shelf : International Bottom Trawl Survey 2021, Dutch Beam Trawl Survey 2020

Abstract: The Marine Strategy Framework Directive (MSFD) requires EU Member States to develop programmes of measures that aim to achieve or maintain Good Environmental Status (GES) in European seas. In order to be able to evaluate the quality status of marine waters on a regular basis and the effects of the measures taken, monitoring programs for MSFD descriptors and indicators have been established by the Member States. The Dutch monitoring program for Marine Litter (D10) includes the collection of data on the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
2
0
1
Order By: Relevance
“…The Dutch BTS 2021 Q3 performed 142 valid hauls, of which 38 were conducted on the Dutch continental shelf. As presented in Figure 2.2, the planned area and amount of hauls per ICES rectangle for 2021 remained generally unchanged compared to those of previous years (Volwater & van Hal 2021). The executed hauls and spatial distribution of litter caught during the Dutch BTS 2021 are presented in Figure 3.6.…”
Section: Bts Q3 2021mentioning
confidence: 92%
See 1 more Smart Citation
“…The Dutch BTS 2021 Q3 performed 142 valid hauls, of which 38 were conducted on the Dutch continental shelf. As presented in Figure 2.2, the planned area and amount of hauls per ICES rectangle for 2021 remained generally unchanged compared to those of previous years (Volwater & van Hal 2021). The executed hauls and spatial distribution of litter caught during the Dutch BTS 2021 are presented in Figure 3.6.…”
Section: Bts Q3 2021mentioning
confidence: 92%
“…Annex 2 Quality -Outlier check 2.1 IBTS Marine litter data from the international IBTS partners was obtained from ICES DATRAS. A data analyses determining the data to be used was done in Volwater & van Hal (2021). It was concluded that Dutch count data was available from 2013 on, French and German count data from 2015 and Danish count data only from 2021 on.…”
Section: Figure Bmentioning
confidence: 99%
“…Aangroeisel op het afval, waaronder mosdiertjes, wordt ook genoteerd. De verzamelingsmethodiek voor het zwerfvuil staat beschreven inVolwater et al (2021).…”
unclassified